Student Dropout Trends in Higher Education of Nepal: A Case Study of Baneshwor Multiple Campus - Kafle, Rameshwor (International Journal of Atharva, 2024)
This study analyzes the pattern of student dropout rates of Baneshwor Multiple Campus (BMC) over the years 2020 to 2022. However, despite BMC’s extensive initiatives, some problems continue to prevail due to social and economic reasons. Dropout rate is influenced by foreign migration more prominently as an aspect of culture wherein people give priority to employment opportunities abroad than study. The data used in this research are obtained from the Educational Management Information System (EMIS), while a scientific method is followed throughout the analysis phase. It is found that different academic levels have dropout rates, which indicate the need for strong retention strategies. The topic discussed in the dialogue covers, among other aspects, the level of effectiveness of the strategy implemented by BMC to reduce college dropouts, as well as external influences on students' lives and the nation's economy arising from student movement.